Alfred Brendel on music collected essays - Brendel, Alfred 1931- (A Cappella Books, 2001)
Noted pianist Alfred brendel brings the clarity and originality of expression that characterize his performance to the printed page. Some of the essays arose from questions for which the available literature did not provide satisfying answers, such as those pertaining to Schubert's piano sonatas, humor in music, the interaction of character and structure, or Beethoven's late style, Others present an overview of Brendel's own endeavors, or special topics such as coping with pianos. Most of the essays were previously published in Musical Thoughts and Afterthoughts (1960) and music Sounded Out (1990).
Teilw. aus dem Dt. übers.
Keywords: Musique - Histoire et critique; Musik; Music -- History and criticism; Klaviermusik; Aufsatzsammlung